THE IMPORTANCE OF NAQSHBANDI IDEAS OF NAVOI IN THE CREATION OF THE FOUNDATION OF THE THIRD RENAISSANCE (Scientific journal of the Fergana State University, 2024)
The article holistically and philosophically examines Sufi ideas in the works of Alisher Navoi. Important aspects of the thinker's views about the perfect person are analyzed. The essence of the idea of humanity in religious and Sufi views is revealed. The philosophical roots and ideological origins of the thinker's views about the perfect person are also highlighted. The significance of Naqshbandi ideas in the work of Alisher Navoi in creating the foundations of the Third Renaissance is substantiated.